Roles of nucleotide metabolism in pancreatic cancer - Liu, Quanlin; Liu, Jiahua; Wang, Shige; Bao, Nabuqi; Zhao, Xinya; Wang, Lei (Frontiers in Immunology, 2025)
Nucleotide metabolism plays a pivotal role in the onset and progression of various human diseases, including pancreatic disorders. As fundamental biomolecules, nucleotides are essential for DNA and RNA synthesis, energy production, and cell signaling. Disruptions in nucleotide metabolic pathways have been linked to altered cell proliferation, apoptosis, and immune responses—critical processes in the development of pancreatic diseases. In pancreatic cancer, metabolic changes in nucleotides facilitate rapid tumor cell proliferation and enhance chemotherapy resistance. Recent studies have concentrated on identifying specific enzymes and pathways within nucleotide metabolism as potential therapeutic targets. Targeted interventions, such as modulating RRM2, TS, and other key enzymes or disrupting the PI3K/AKT/mTOR pathway, have demonstrated potential in reducing tumor growth and inflammation in pancreatic tissue. This review provides an overview of the latest advancements in the understanding of nucleotide metabolism in pancreatic cancer pathogenesis, emphasizing diagnostic and therapeutic strategies that may improve patient outcomes.